2012
DOI: 10.1002/mrm.24510
|View full text |Cite
|
Sign up to set email alerts
|

In vivo1H-MRS hepatic lipid profiling in nonalcoholic fatty liver disease: An animal study at 9.4 T

Abstract: The applicability of the in vivo proton magnetic resonance spectroscopy hepatic lipid profiling (MR-HLP) technique in nonalcoholic fatty liver disease was investigated. Using magnetic resonance spectroscopy, the relative fractions of diunsaturated (fdi), monounsaturated (fmono), and saturated (fsat) fatty acids as well as total hepatic lipid content were estimated in the livers of 8 control and 23 CCl4-treated rats at 9.4 T. The mean steatosis, necrosis, inflammation, and fibrosis scores of the treated group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In the first session, in addition to HCL measurements, T 2 measurements were performed with the GUSTEAU sequence using eight TEs (6,10,15,20,30,40,50 and 70 ms). The TEs were optimized for fast measurement of the monoexponential decay of the hepatic lipids.…”
Section: Measurements Of Hcl Repeatability and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first session, in addition to HCL measurements, T 2 measurements were performed with the GUSTEAU sequence using eight TEs (6,10,15,20,30,40,50 and 70 ms). The TEs were optimized for fast measurement of the monoexponential decay of the hepatic lipids.…”
Section: Measurements Of Hcl Repeatability and Tmentioning
confidence: 99%
“…Although MRI can cover the entire liver tissue, MRS is currently the most accurate non‐invasive method for the assessment of hepatic steatosis . In vivo MRS measurements of HCL have already been validated against the histological analysis of tissue specimens from animals at 9.4 T and in humans at clinical field strengths (≤3 T) . As a result of the water signal and motion, FA profiling in the liver is more complicated than in adipose tissue or bone marrow .…”
Section: Introductionmentioning
confidence: 99%
“…Proton MRS studies have shown levels and composition of fat to be relevant to the study of a number of diseases such as cancer, obesity, osteoporosis and liver disease . The fat olefinic (≈5.4 parts per million, ppm) resonance yields a measure of fat unsaturation, and olefinic levels normalized to methylene (≈1.3 ppm) or methyl (≈0.9 ppm) signals have been used to estimate measures of fat unsaturation in humans in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Using magnetic resonance spectroscopy (MRS) for this analysis, highly accurate quantification of the occurring signal parts is of great importance to get reliable information about the composition of body fat. Especially, precise assessment of monounsaturated and polyunsaturated fatty acids has become an important task for metabolic studies on obesity and type 2 diabetes (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…. ; yðl þ L À 1Þ T at the time instants 0 l N À L. If q k ðnÞ from Eq [6]. only changes slowly in an interval of the length L it can be replaced in each measurement vector with its Taylor-series approximation.…”
mentioning
confidence: 99%